1999
DOI: 10.1111/j.1748-5827.1999.tb03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible immunodeficiency in related rottweiler dogs

Abstract: A litter of eight rottweiler pups is described in which two dogs died before the age of six months from systemic inflammatory disease, and two further pups developed inflammatory skin disease. All seven pups tested had a markedly low serum immunoglobulin A (IgA) concentration (< 0.1 mg/ml) and six of these dogs also had subnormal serum IgG (< 0.1 to 6.4 mg/ml). Tissues taken from three diseased pups were examined immunohistochemically using a number of lymphoid markers. Secondary lymphoid tissues had a paucity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
0
13
1
2
Order By: Relevance
“…However, there was a significant effect within pedigree dogs: the highest case fatality rates were estimated for hounds, non-sporting dogs and gundogs, and the lowest fatality rates were estimated for terriers and working dogs. This trend may be due to differences in immune competence between specific breeds as immunological nonresponsiveness is thought to be controlled genetically, although interestingly pedigree types at greater risk of death in this study do not correlate with those specific breeds previously reported to be at greatest risk of CPV infection (Rottweiler, Doberman pinscher, German shepherd, American pit bull terrier, Labrador retriever, Springer spaniel, and Yorkshire terrier) (Day, 1999;Glickman et al, 1985;Goddard and Leisewitz, 2010;Godsall et al, 2010;Smith-Carr et al, 1997). An estimated 0.1% of dogs in general are non-responsive to CPV vaccines and whilst this lack of response is genetically controlled it is seen across breeds (Welbon et al, 2011).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, there was a significant effect within pedigree dogs: the highest case fatality rates were estimated for hounds, non-sporting dogs and gundogs, and the lowest fatality rates were estimated for terriers and working dogs. This trend may be due to differences in immune competence between specific breeds as immunological nonresponsiveness is thought to be controlled genetically, although interestingly pedigree types at greater risk of death in this study do not correlate with those specific breeds previously reported to be at greatest risk of CPV infection (Rottweiler, Doberman pinscher, German shepherd, American pit bull terrier, Labrador retriever, Springer spaniel, and Yorkshire terrier) (Day, 1999;Glickman et al, 1985;Goddard and Leisewitz, 2010;Godsall et al, 2010;Smith-Carr et al, 1997). An estimated 0.1% of dogs in general are non-responsive to CPV vaccines and whilst this lack of response is genetically controlled it is seen across breeds (Welbon et al, 2011).…”
Section: Discussioncontrasting
confidence: 67%
“…Unvaccinated puppies aged between six weeks and six months are at greatest risk of developing CPV-related disease, and the incidence of disease is also greater in the warmer months of the year (Godsall et al, 2010;Horner, 1983;Smith-Carr et al, 1997). The reported predisposition of certain breeds -including Rottweiler, Doberman pinscher, German shepherd, American pit bull terrier, Labrador retriever, Springer spaniel and Yorkshire terrier (Day, 1999;Glickman et al, 1985;Goddard and Leisewitz, 2010;Godsall et al, 2010;Smith-Carr et al, 1997) -suggests genetic susceptibility to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Serum IgE concentration in stray dogs with dermatologic problem was significantly higher (P<0.001) than that of The significant increases of IgE concentrations were observed in the cases of flea-bite dermatitis, atopic dermatitis and food allergy 6,9 . Taszkun 10 found polysensitization in 98.6% of dogs with atopic dermatitis in intradermal skin tests.…”
Section: Discussionmentioning
confidence: 82%
“…Similarly, it has been suggested that measurement of IgE using ELISA was a reliable method (93-97%) in the diagnosis of atopic dermatitis in dogs 5 . Day 6 , has suggested that markedly low serum IgA and subnormal serum IgG concentrations was found in Rottweiler pups with inflammatory skin diseases. In the majority of canine cases of bacterial diseases, hypersensitivity disorders, endocrine dermatosis, dermatomycosis, parasitic disease, cutaneous Leishmaniasis and non-specific dermatopathies of uncertain aetiology were found to show intercellular deposits of IgG, M and A in skin sections…”
Section: öZetmentioning
confidence: 99%
“…The median IgA concentrations for both Scandinavian sample groups were below the chosen arbitrary cut-off of 0.1 g/l. Previously suggested cut-offs in different dog breeds include 0.3 g/l (Moroff et al, 1986), 0.22 g/l (Day and Penhale, 1988), 0.18 g/l (Felsburg et al, 1985), and 0.15 g/l (Day, 1999;Rivas et al, 1995) and thus, higher as compared to the cutoff we chose. The median IgA concentration was 0.035 g/l (mean = 0.045 g/l, SD = 0.061 g/l) for the 58 samples from freeranging wolves from the first sample group and 0.076 g/l (mean = 0.102 g/l, SD = 0.183 g/l) for the 92 samples from the second sample group.…”
Section: Resultsmentioning
confidence: 99%